Experimental and Numerical Studies on the Vertical Flow of Variable Density Fluid in Different Directions - Zhifang Zhou; Boran Zhang; Qiaona Guo; Shumei Zhu (Geofluids)
Injecting freshwater and pumping salt water are effective methods to restore the salt water in a coastal area. Based on a one-dimensional vertical experiment, the variable density flow is simulated under the condition of different injection directions and injection rates of fresh water. A one-dimensional mathematical model of variable density flow and solute transport is established. The mathematical models are solved using the implicit difference method. Fortran code is developed to simulate and verify the vertical flow of variable density flow in different directions. Through both numerical simulation and experimental studies, it is found that the variable density fluid in the direction of reverse gravity is different from that in the direction of gravity. On this basis, the most effective desalination model of salt water is further discussed. It provides a theoretical and technical method for the restoration of salt water in the vertical injection of freshwater. In order to improve the remediation efficiency and reduce the cost in the engineering application, the suitable water injection rate should be ensured, considering the suitable construction time and zone of a study area.